2015
DOI: 10.4236/oalib.1101808
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Isolated from the Oropharynxs of Apparently Healthy Chickens in Jos, Nigeria

Abstract: There are concerns that apparently healthy chickens may transmit potentially pathogenic pathogens that could threaten not only poultry industry, but also public health. This investigative study was carried out in Jos, Nigeria to determine the prevalent bacterial agents in the oropharynxs of apparently healthy chickens. Four hundred (400) oro-pharyngeal swabs were collected from 400 apparently healthy chickens for bacteriological analysis. Swab from each sample was cultured on 7% defibrinated sheep blood, Casei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…(63%) associated with bile and intestinal content of slaughtered chickens, but significantly higher than the finding of Puspandari et al [ 37 ], who reported an 8.8% prevalence rate from Indonesia. It was shown to be greater than the study conducted in Egypt, which revealed a 10% prevalence of Klebsiella pneumoniae , Dashe et al [ 38 ], reported 8.8%, and Popy et al [ 39 ], who reported a 6% prevalence of Klebsiella spp. Also, it was higher than the report of Bushen et al [ 40 ], who identified 22.6% of Klebsiella pneumoniae from chicken in Ethiopia.…”
Section: Discussionmentioning
confidence: 74%
“…(63%) associated with bile and intestinal content of slaughtered chickens, but significantly higher than the finding of Puspandari et al [ 37 ], who reported an 8.8% prevalence rate from Indonesia. It was shown to be greater than the study conducted in Egypt, which revealed a 10% prevalence of Klebsiella pneumoniae , Dashe et al [ 38 ], reported 8.8%, and Popy et al [ 39 ], who reported a 6% prevalence of Klebsiella spp. Also, it was higher than the report of Bushen et al [ 40 ], who identified 22.6% of Klebsiella pneumoniae from chicken in Ethiopia.…”
Section: Discussionmentioning
confidence: 74%